REPRESENTASI MITOS BATIYANAN PADA MASYARAKAT BANJAR - Rissari Yayuk (UNDAS: Jurnal Hasil Penelitian Bahasa dan Sastra, 2018)
This study aims to describe the use of myth in the Banjar culture. Myth contains implicit communication purpose and meaning that can be known through the study of pragmatic study. The problems in this study are 1) how does the representation of Banjarese myth base on the form of communication? 2) how does the representation of Banjarese myth base on the communication function? The aims of this study are to describe 1) the representation of batiyanan myth in Banjar society base on the form of communication. 2) the representation of batiyanan myth in Banjar soiety base on the communication function. This research is a qualitative research using descriptive method. The data are taken from Banjarese speech in Kampung Jawa, Sekumpul, Martapura Regency. The data are taken from January 2017 to June 2017. Data collection techniques are note taking and interviewing. Data collection techniques are interview and documentation. This study uses three steps of work, they are (1) providing data; (2) data analyzing; and (3) presenting the results of the data analysis. This study uses pragmatic theory. The results conclude that 1) base on the form of communication, the representation of batiyanan myth in Banjar society consists of indirect speech with declarative structure in the form of directive speech and commisive; 2) base on the communication function , the representation of batiyanan myth in Banjar society consists of advice function happens if the speakers try to give advice, prohibition function happens if there is prohibition marker, satire function happens if the speaker intend to criticize the speech partner indirectly, and threats function happens if the speech has violation meaning and it cause something bad happen in the future.